Manufacture and Testing of Belt Grinding Development - Zulmaidas, Ikhsan; Syahrul, Syahrul; Ambiyar, Ambiyar; A, Yufrizal (Universitas Negeri Padang, 2019)
The lack of utilization of belt grinding, especially in the world of education due to lack of public understanding of the workmanship of belt grinding. This study discusses the process of developing belt grinders from the manufacturing stage to testing. The purpose of this study is to develop belt grinders of existing forms, to maximize their function. The belt burrs resulting from this development have three functions, namely the vertical, angle and horizontal cutting function. This belt burrs are also equipped with speed control. With the development of this belt grinder, it is hoped that it will add to the public's insight into the belt grinding function and better assist the work of grinding, especially grinding finishing.